The human gut microbiota is associated with host lifestyle: a comprehensive narrative review - Zeng, Qin; Feng, Xianqiong; Hu, Yanling; Su, Shaoyu (Frontiers in Microbiology, 2025)
BackgroundThe gut microbiota serves as a critical interface between lifestyle factors and host physiology. Despite extensive research on individual domains including diet, sleep, and exercise, an integrated understanding of their synergistic effects on microbial communities remains incomplete. This knowledge gap limits our ability to develop targeted microbiome-based interventions for metabolic and immune-related disorders.MethodsTo address this gap, we conducted a comprehensive evaluation of peer-reviewed literature from 2000 to present, identified through systematic searches of PubMed, Web of Science, and Scopus using key terms related to gut microbiota and lifestyle interventions. Our analysis focused on studies incorporating microbiome profiling techniques, controlled lifestyle interventions, and multi-omics data integration. The review prioritized mechanistic insights from both clinical and preclinical investigations while critically assessing methodological approaches across the field.ResultsHigh-fiber dietary patterns consistently promoted the abundance of beneficial, short-chain fatty acid-producing bacteria, though with notable inter-individual variation. Circadian rhythm disruption was associated with reduced microbial diversity and expansion of pro-inflammatory bacterial taxa, paralleling increases in systemic inflammation markers. Athletic populations demonstrated unique microbial signatures characterized by enhanced metabolic potential, with distinct taxonomic profiles emerging across different sport disciplines.ConclusionThis work synthesizes current evidence into a novel framework for understanding lifestyle-microbiota interactions, while identifying key challenges in study design and data interpretation. We propose standardized methodological approaches for future investigations and outline translational strategies for personalized microbiota modulation. These insights advance the potential for targeted microbial interventions to optimize metabolic and immune health outcomes.